Upaya pendidikan sebagai fasilitator dalam menanamkan nilai kesetaraan gender terhadap remaja - Ais zahra, Sabrina; Khasanah, Nur (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
Gender equality is a fundamental principle that emphasizes individuals' equal rights regardless of sex. However, in reality, the issues of equality are not yet fully understood or implemented by Indonesian society and need to be addressed wisely. This study uses a qualitative descriptive research method with a literature review. The data collection method was obtained through 1 book reference and 10 scientific journals, as well as other documents relevant to the discussion of this study. The nature of this literature review research involves systematically presenting the collected data and providing detailed explanations to readers to enhance understanding. The findings of this study suggest that one of the methods to achieve gender equality is through guidance from education so that it can be applied in society. Education serves as the main facilitator and provides fundamental values to help reduce the traces of gender inequality, especially among adolescents. Because during this period, they are easily influenced by negative things that can affect their behavior towards gender equality. Education is not only obtained in the school environment; the family scope is also one of the means to gain new knowledge about the importance of gender equality. Therefore, with proper education, it will shape teenagers' mindsets to be able to become positive agents of change who have an impact on society.